Mamíferos prioritários para conservação e uso de hábitat pelo tatu-bola em uma área antropizada no Nordeste do Brasil - Rodolfo Assis Magalhães (2020)
Conservation planning relies typically on spatial data on the distribution of sufficiently known elements of biodiversity (i.e., biodiversity surrogates), but an effective conservation may only be achieved by considering social factors that can influence the success of conservation actions as well as by understanding the biology of the organisms to be protected. However, there is still a lack of information on the biology and conservation of threatened species, such as the Brazilian three-banded armadillo Tolypeutes tricinctus. Here, we aimed to: (i) identify priority species for conservation based on their official conservation status and the humanfauna relationships (i.e., ethnozoology) in the rural community of Sumidouro, northeastern Brazil; and (ii) investigate the habitat use by T. tricinctus in the same area. We used camera traps, active searching and a set of participatory methods, including semi-structured interviews, to assess mammal diversity and ethnozoology (potential cultural keystone species - CKS, charismatic/popular and disliked/unpopular species, and most hunted species) for prioritization. We used camera traps, active searching and occupancy models to explore the influence of ecological and methodological factors, including human-related habitat features, on the occupancy and detection probabilities of T. tricinctus. We prioritized 11 species for conservation, of which we considered Panthera onca and Tolypeutes tricinctus top-priorities, due to their especially worrying conservation status. We also prioritized Mazama sp., because it was considered the most hunted and popular species as well as a potential CKS in the past. Due to their great popularity and high level of threat, we considered Tolypeutes tricinctus and Mazama sp. the most recommended species to be used as flagships for conservation. Regarding habitat use by T. tricinctus, we found its occupancy probability high and constant throughout the study area. Meanwhile, its detection probability was influenced by the sampling method, being almost 10 times greater by active searching than camera trapping. Therefore, we found that T. tricinctus may be widely distributed in anthropized areas. We also reinforced the need for combining different sampling methods and take detection bias into account to draw reliable inferences about ecological processes. Based on the widespread distribution and the great popularity of T. tricinctus in our study area, together with its worrying conservation status, we believe this population of the species is a priority for conservation actions and research projects. We also highlight the need and feasibility of the conservation of Mazama sp. in our study area, as well as the need for human-fauna coexistence projects to promote the conservation of Panthera onca, the most threatened and